DALES, Drug Allergy Labels in Elective Surgical patients: a prospective multicentre cross-sectional study of incidence, risks, and attitudes in penicillin de-labelling strategies. (December 2020) - Savic, Louise; Thomas, Caroline; Fallaha, David; Wilson, Michelle; Hopkins, Philip M.; Savic, Sinisa; Clark, Samuel H.; ,
Abstract: Background: Penicillin allergy is associated with a range of poor health outcomes. Allergy testing can be made simpler by using a direct drug provocation test in patients at low risk of genuine allergy. This approach could allow population-level 'de-labelling'. We sought to determine the incidence and nature of penicillin allergy labels in UK surgical patients and define patient and anaesthetist attitudes towards penicillin allergy testing. Methods: A prospective cross-sectional questionnaire study was performed in 213 UK hospitals. 'Penicillin allergic' patients were interviewed and risk-stratified. Knowledge and attitudes around penicillin allergy were defined in patients and anaesthetists. Results: Of 21 219 patients, 12% ( n =2626) self-reported penicillin allergy; 27% reported low-risk histories potentially suitable for a direct drug provocation test; an additional 40% reported symptoms potentially suitable for a direct drug provocation test after more detailed assessment. Of 4798 anaesthetists, 40% claimed to administer penicillin routinely when they judged the label low risk. Only 47% of anaesthetists would be happy to administer penicillin to a patient previously de-labelled by an allergy specialist using a direct drug provocation test; perceived lack of support was the most common reason for not doing so. Conclusions: At least 27% of patients with a penicillin allergy label may be suitable for a direct drug provocation test. Anaesthetists demonstrated potentially unsafe prescribing in patients with penicillin allergy labels. More than half of anaesthetists lack confidence in the results of a direct drug provocation tests undertaken by a specialist. Our findings highlight significant barriers to the effective implementation of widespread de-labelling in surgical patients.